2019
DOI: 10.1101/552851
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The human non-visual opsin OPN3 regulates pigmentation of epidermal melanocytes through interaction with MC1R

Abstract: Opsins form a family of light-activated, retinal-dependent G-protein coupled receptors (GPCRs) that serve a multitude of visual and non-visual functions. Opsin3 (OPN3 or encephalopsin), initially identified in the brain, remains one of the few members of the mammalian opsin family with unknown function and ambiguous light-absorption properties. We recently discovered that OPN3 is highly expressed in human epidermal melanocytes-the skin cells that produce melanin. The melanin pigment is a critical defense again… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(18 citation statements)
references
References 59 publications
2
16
0
Order By: Relevance
“…This was a major concern of ours even before generating the OPN3-mCh mouse model and we took precautions to the best of our ability to ensure that OPN3-mCh maintained endogenous localization. In our previous publication, we identified that OPN3 subcellular localization in melanocytes and other heterologous cell types is at the plasma membrane, as expected of a GPCR, but also in internal vesicles within the cytoplasm; OPN3-mCh significantly colocalized with endogenous OPN3 (using the now discontinued OPN3 antibody) in primary human melanocytes (Ozdeslik et al, 2019). In addition to retaining its subcellular localization, we found that OPN3-mCh retained its regulatory activity in melanocytes, suggesting that OPN3-mCh is functional despite fusion to a fluorescent protein (Ozdeslik et al, 2019).…”
Section: Discussionmentioning
confidence: 72%
See 4 more Smart Citations
“…This was a major concern of ours even before generating the OPN3-mCh mouse model and we took precautions to the best of our ability to ensure that OPN3-mCh maintained endogenous localization. In our previous publication, we identified that OPN3 subcellular localization in melanocytes and other heterologous cell types is at the plasma membrane, as expected of a GPCR, but also in internal vesicles within the cytoplasm; OPN3-mCh significantly colocalized with endogenous OPN3 (using the now discontinued OPN3 antibody) in primary human melanocytes (Ozdeslik et al, 2019). In addition to retaining its subcellular localization, we found that OPN3-mCh retained its regulatory activity in melanocytes, suggesting that OPN3-mCh is functional despite fusion to a fluorescent protein (Ozdeslik et al, 2019).…”
Section: Discussionmentioning
confidence: 72%
“…In our previous publication, we identified that OPN3 subcellular localization in melanocytes and other heterologous cell types is at the plasma membrane, as expected of a GPCR, but also in internal vesicles within the cytoplasm; OPN3-mCh significantly colocalized with endogenous OPN3 (using the now discontinued OPN3 antibody) in primary human melanocytes (Ozdeslik et al, 2019). In addition to retaining its subcellular localization, we found that OPN3-mCh retained its regulatory activity in melanocytes, suggesting that OPN3-mCh is functional despite fusion to a fluorescent protein (Ozdeslik et al, 2019). Although there is a possibility that OPN3 processing may lead to altered subcellular localization of OPN3-mCh, we believe this is unlikely, as tagging other GPCRs at the direct C terminus with fluorescent proteins and using similar knock-in methods did not alter subcellular localization (as in the MC4R-GFP mouse; Siljee et al, 2018).…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations